A Case of Type 2 Amiodarone-Induced Thyrotoxicosis That Underwent Total Thyroidectomy under High-Dose Steroid Administration. (13th January 2015) - Hashimoto, Koshi; Ota, Masaki; Irie, Tadanobu; Takata, Daisuke; Nakajima, Tadashi; Kaneko, Yoshiaki; Tanaka, Yuko; Matsumoto, Shunichi; Nakajima, Yasuyo; Kurabayashi, Masahiko; Oyama, Tetsunari; Takeyoshi, Izumi; et al.
Abstract : Amiodarone is used commonly and effectively in the treatment of arrhythmia; however, it may cause thyrotoxicosis categorized into two types: iodine-induced hyperthyroidism (type 1 amiodarone-induced thyrotoxicosis (AIT)) and destructive thyroiditis (type 2 AIT). We experienced a case of type 2 AIT, in which high-dose steroid was administered intravenously, and we finally decided to perform total thyroidectomy, resulting in a complete cure of the AIT. Even though steroid had been administered to the patient (maximum 80 mg of prednisolone), the operation was performed safely and no acute adrenal crisis as steroid withdrawal syndrome was found after the operation. Few cases of type 2 AIT that underwent total thyroidectomy with high-dose steroid administration have been reported. The current case suggests that total thyroidectomy should be taken into consideration for patients with AIT who cannot be controlled by medical treatment and even in those under high-dose steroid administration.